Acute anodal transcranial direct current stimulation improves the performance of professional rowers - Luciano Ramos; Luciano Ramos; Tatiana Aparecida Magacho Ramos; Tatiana Aparecida Magacho Ramos; Rodrigo Freire De Almeida; Rodrigo Freire De Almeida; Jader Vinicius da Silva-Rocha; Jader Vinicius da Silva-Rocha; Carla Zimerer; Carla Zimerer; Fernando Zanela Arêas; Fernando Zanela Arêas; et al. (Frontiers Media S.A., 2024)
IntroductionThe aim of the present study was to evaluate the influence of acute transcranial direct current stimulation (tDCS) on physical and subjective responses in professional rowing during the 2,000-m time trial test.MethodsSeven rowers (age 20.86 ± 4.49 years; weight 71.66 ± 7.97 kg) participated in this randomized triple-blind trial with a crossover experimental design. The protocol consists of 2 days with different conditions (anodal and sham). The tDCS anodic stimulation conducted was 2 mA for 20 min in the left temporal cortex (2.5 cm from the F7 zone and 2.5 cm from the T3 zone), targeting the left insular cortex. In the sham moment, the participants experienced 30 s of stimulation. Afterward, they performed a standardized progressive warm-up for 15 min, following the Brazilian Rowing Confederation's assessment protocols, and rested for 3 min before the test started. All procedures were made on an indoor rowing machine, which allowed the capture of performance variables such as time performed, power in watts (W), pace (m/min), and stroke rate (strokes/min). The ratings of perceived exertion [Borg scale (CR-20)] were recorded in each 2-min during the test.ResultsThe results presented differences in power [Z: −2.371; p = 0.018; effect size (ES) = −0.896 (large)] and pace [Z: −2.371; p = 0.018; ES = −0.896 (large)] and time performance [Z: −1.612; p = 0.107; ES = −0.609 (large)] throughout the protocol for the anodal moment.DiscussionHowever, no differences for the other variables were found. According to the results, the current tDCS with the present protocol improved the physical performance at the 2,000-m time trial Test providing ergogenic aid.